THE PERFORMANCE OF YOUTH, SPORT, AND TOURISM SERVICE (DISPORA) IN DEVELOPING TOURIST POTENCY IN WONOGIRI REGENCY (A Case Study on Tourism Division of Youth, Sport, and Tourism Service of Wonogiri Regency) - Ida Rahayu Ningsih, Winarti, Joko Suranto (Solidaritas, 2018)
ABSTRACT This research aimed to analyze the organizational performance of Youth, Sport, and Tourism Service (Dispora) of Wonogiri Regency, particularly in tourism division. This study was a descriptive qualitative research with case study method. Techniques of collecting data used were: (1) observation, (2) interview, and (3) documentation. To measure the performance of public organization, in this research the author employed five indicators developed by Agus Dwiyanto, et al., consisting of: (1) productivity, (2) service quality, (3) responsibility, (4) responsiveness, and (5) accountability, while the analysis model used was an interactive one developed by Mathew B, Miles, A. Michael Huberman and Johnny Saldana encompassing: (1) data collection/reflection, (2) data display, (3) data reduction, and (4) Conclusion. Overall, the result of research was good, as indicated with the following results: (1) the performance of tourism division in DISPORA of Wonogiri Regency, viewed from productivity aspect, was fair (sufficiently good) and had been effective; (2) the performance of tourism division in DISPORA of Wonogiri Regency, viewed from service quality, was still low; (3) the performance of tourism division in DISPORA of Wonogiri Regency, viewed from Responsiveness, was sufficiently good (fair); (4) the performance of tourism division in DISPORA of Wonogiri Regency, viewed from Responsibility, had been good; and (5) the performance of tourism division in DISPORA of Wonogiri Regency, viewed from Accountability, had been sufficiently good (fair). Keywords: Performance, Organization, Tourism